Patterns of journal use by undergraduates in university of Ibadan, Nigeria (2010)
Journal use by undergraduates in University of Ibadan was investigated to determine the purpose, frequency of use and challenges militating against its use. Undergraduates from Education, Science, Social Sciences and Technology were randomly selected to give a sample size of 154 and a questionnaire was used for data collection. Undergraduates in Technology were the highest users journal for class work (50.0%) and research work (42.2%), while 83.3% of those in Science used CDROM as access point to journals. Weekly use of journals was found to be highest for those in Technology. Undergraduates in all the disciplines attributed power supply as a major factor affecting journal use, while those in the Social Sciences agreed that inadequate ICT skills (36.0°/o), inadequate ICT (35.0%) and difficulty locating journals (27.8%) were the major factors that affected their use of journals. Improved use of journals would be achieved when these challenges are eradicated.